THE IMPACT OF NEW NORMAL REGULATION TO THE IMPLEMENTATION OF SCL APPROACH IN SECONDARY LEVEL - Akrim Akrim; Dina Mardiana (Ta'dib, 2020)
Abstract: The purpose of the research was  to evaluate the implementation of KKNI based curriculum.  This study used a qualitative approach, case study. The data collection techniques were interviews, observation, and documentation. The data were analyzed by using Miles and Huberman techniques. The results of the research show four variables that were evaluated. From the result of data analysis it was found that First, in the aspect of the context variable, the perception of lecturers and students about curriculum implementation based on KKNI was already good, but the perceptions of the educational staffs were not good. Second, in terms of the input variable, it was seen from three points; the vision and mission, KKNI socialization, and learning management. Third, from the aspect of the process variable, in the learning process, the lecturers of Faculty of Tarbiyah and Teacher Training (FITK) tended to have implemented student- centered learning. Meanwhile the lecturers of Faculty of Sharia and Law (FSH) still tended to implement teacher- centered learning processes. Fourth, in terms of product variable, the achievement of the students who took curriculum class in reference to KKNI were very good.Abstrak: Tujuan penelitian ini adalah untuk mengevaluasi pelaksanaan kurikulum berbasis KKNI. Penelitian ini menggunakan pendekatan kualitatif studi kasus. Teknik pengumpulan data adalah wawancara, observasi, dan dokumentasi. Analisis data menggunakan teknik Miles dan Huberman. Hasil penelitian menunjukkan empat variabel yang dievaluasi. Dari hasil analisis data diketahui bahwa Pertama, pada aspek variabel konteks, persepsi dosen dan mahasiswa tentang penerapan kurikulum berbasis KKNI sudah baik, namun tenaga kependidikan kurang baik. Kedua, ditinjau dari variabel input dilihat dari tiga poin; visi dan misi, sosialisasi KKNI, dan manajemen pembelajaran. Ketiga, dari aspek variabel proses, dalam proses pembelajaran dosen Fakultas Tarbiyah dan Keguruan (FITK) cenderung menerapkan pembelajaran yang berpusat pada siswa. Sementara dosen Fakultas Syariah dan Hukum (FSH) masih cenderung menerapkan proses pembelajaran yang berpusat pada guru. Keempat, ditinjau dari variabel produk, prestasi belajar siswa yang mengikuti kelas kurikulum mengacu pada KKNI sangat baik.